2018
DOI: 10.5688/ajpe6296
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Student Knowledge, Confidence and Attitudes Toward Medical Cannabis and Curricular Coverage

Abstract: Objective. To assess pharmacy student confidence in their knowledge of qualifying conditions for medical cannabis use in the US and their attitudes toward curricular coverage of medical cannabis. Methods. Students were asked to complete an electronic survey to measure knowledge and confidence in various domains of medical cannabis treatment, including qualifying conditions, adverse effects, and other patient care skills. Results. There were 238 students who completed the survey. Responses to all domains and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 19 publications
5
36
1
Order By: Relevance
“…The results of the current study demonstrate that nursing students have a poor knowledge of the potential uses of medical marijuana, as well as the risks associated to it, which corroborates findings from previous studies suggesting that healthcare students need more training on medical marijuana [21,[24][25][26]. The students did not know either authorized indications or non-authorized ones.…”
Section: Discussionsupporting
confidence: 82%
“…The results of the current study demonstrate that nursing students have a poor knowledge of the potential uses of medical marijuana, as well as the risks associated to it, which corroborates findings from previous studies suggesting that healthcare students need more training on medical marijuana [21,[24][25][26]. The students did not know either authorized indications or non-authorized ones.…”
Section: Discussionsupporting
confidence: 82%
“…Surveys of pharmacy students have shown more than half of pharmacy students support MC legalization, with a recent survey showing an 85% acceptance rates in 2018 at a private pharmacy school in the Midwest. 10,11 Some states have moved to include pharmacists in the dispensing of MC in some capacity. 2 Connecticut, Minnesota, New York, and Pennsylvania require a pharmacist or a health care professional, depending on the state, to be onsite at MC dispensaries, whereas Arkansas requires dispensaries to appoint a pharmacist consultant.…”
mentioning
confidence: 99%
“…However, surveys of pharmacists and pharmacy students have shown that more training and education is necessary to answer clinical questions on MC. 10,11,[19][20][21] Three published studies have assessed pharmacy student knowledge about MC. 10,11,19 Two studies were conducted at Midwestern pharmacy schools where MC was illegal, in 2011 and 2017.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A 2017 study demonstrated that student pharmacists largely felt nonconfident in discussing risks of medical cannabis use with patients. 19 In line with evidence-based medicine, student pharmacists also recognized the need for more research with these agents to inform curricular expansion regarding pharmacologic impacts for patients. In addition to the potential therapeutic implications of cannabis and related products, the diverse legal landscape regarding cannabis and related products adds additional nuances to be understood by student pharmacists and pharmacists.…”
Section: 1daddressing Professional Burnoutmentioning
confidence: 99%